Peran Pola Asuh Otoritatif dan Efikasi Diri Terhadap Kesejahteraan Psikologis Pada Remaja Akhir Mahasiswa di Universitas Udayana - Diatmika Karna, Ida Ayu Bulan Kania; Lestari, Made Diah (Jurnal Ilmiah Wahana Pendidikan, 2024)
The psychological dynamics of late adolescence are related to the ego to learn new things, a settled sexual identity and separating private and public things. In addition, late adolescence is labeled as the most impressive age for individuals, because individuals will get new responsibilities and roles in society. Some of the problems that haunt late adolescents are emotional immaturity and relationships with families, which have an impact on late adolescent self-adjustment. One example of the manifestation of late adolescence is new students. This study aims to look at the role of authoritative parenting and self-efficacy on psychological well-being in late adolescent students at Udayana University. The sampling technique in this study is probability sampling type multistage cluster sampling. Respondents in this study amounted to 180 Udayana University students. The Psychological Well-Being Scale has an Alpha coefficient of 0,871, the Authoritative Parenting Scale has an Alpha coefficient of 0,850 and the Self-Efficacy Scale has an Alpha coefficient of 0,880. This study used multiple regression tests. The results of this study state that authoritative parenting and self-efficacy together play a role in improving the psychological well-being of late adolescents at Udayana University. In addition, authoritative parenting and self-efficacy play a positive role in improving the psychological well-being of late adolescents at Udayana University.